Left Ventricular Diastolic Dysfunction Assessed by Conventional Echocardiography and Spectral Tissue Doppler Imaging in Adolescents With Arterial Hypertension. Issue 8 (February 2016) - Morka, Aleksandra; Szydlowski, Leslaw; Moric-Janiszewska, Ewa; Mazurek, Boguslaw; Markiewicz-Loskot, Grazyna; Stec, Sebastian
Abstract : Abstract: Compared to conventional echocardiography, spectral tissue Doppler imaging (s-TDI) allows more precise evaluation of diastolic cardiac function. The purpose of this study was to conduct s-TDI to analyze the slow movement of the left ventricular (LV) myocardium in adolescents with systemic arterial hypertension (HT) and to determine whether patients with HT suffer from LV diastolic dysfunction. The study group comprised 69 consecutive patients (48 boys and 21 girls aged 14–17 years [mean, 15.5 ± 1.1 years]) with primary HT, and the control group comprised 48 healthy participants (24 boys and 24 girls aged 14–17 years [mean, 15.8 ± 1.3 years]). Physical examinations, 24-hour arterial blood pressure monitoring, conventional 2-dimensional and Doppler echocardiography, and s-TDIs were performed. Analysis revealed that study group participants were significantly heavier and had greater LV mass indices than controls ( P < 0.001). There were no differences between the velocities of E waves (peak early filling of mitral inflow), but the deceleration times of the mitral E waves were significantly shorter whereas the A waves survived longer in the study group than in the control group. The velocities of A waves (peak late filling of mitral inflow) were elevated ( P = 0.041), and the E/A wave pattern (E/A = 1.8 ± 0.4) was normal. These results suggest pseudonormalization, a type of LV diastolic dysfunction in adolescents with HT. In the study group, when the sample volume was positioned at the septal or lateral insertion site of the mitral leaflet, the e′ wave velocity was significantly depressed whereas the a′ wave velocity was elevated, compared to those of the control group ( P < 0.001). The e′/a′ ratios from the septal and lateral insertion sites were lower, whereas the E/e′ ratio from the septal insertion site was significantly higher in the study group, similar to that seen in atrial reversal velocity ( P < 0.001). These findings indicate that using sTDI to find and measure diastolic LV failure is valuable when the probe is placed at the septal and lateral mitral valve annuli during examination. Changes in the myocardium appear similar to those seen in adults.